Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s11357-016-9940-z
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific correlation between red blood cell mitochondrial ROS production, cardiolipin content and longevity in birds

Abstract: Mitochondrial respiration releases reactive oxygen species (ROS) as by-products that can damage the soma and may in turn accelerate ageing. Hence, according to "the oxidative stress theory of ageing", longer-lived organisms may have evolved mechanisms that improve mitochondrial function, reduce ROS production and/or increase cell resistance to oxidative damage. Cardiolipin, an important mitochondrial innermembrane phospholipid, has these properties by binding and stabilizing mitochondrial inner-membrane protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 61 publications
(67 reference statements)
0
31
0
Order By: Relevance
“…; Delhaye et al . ). Interestingly, it is now possible to simultaneously record O 2 consumption and fluorescence signal, using the O2k‐fluorescence module (Oroboros Instruments, Innsbruck, Austria) that could be added to the O2k‐Oroboros device that we used in this study.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…; Delhaye et al . ). Interestingly, it is now possible to simultaneously record O 2 consumption and fluorescence signal, using the O2k‐fluorescence module (Oroboros Instruments, Innsbruck, Austria) that could be added to the O2k‐Oroboros device that we used in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Assessing ROS production is challenging, but has already being done using fluorescent probes in non-mammalian vertebrate RBCs (e.g. Olsson et al 2008;Stier et al 2014a;Delhaye et al 2016). Interestingly, it is now possible to simultaneously record O 2 consumption and fluorescence signal, using the O2k-fluorescence module (Oroboros Instruments, Innsbruck, Austria) that could be added to the O2k-Oroboros device that we used in this study.…”
Section: O R R E L a T I O N S B E T W E E N M I T O C H O N D R I mentioning
confidence: 99%
See 1 more Smart Citation
“…According to our study, species with longer lifespan suffer less oxidative damage to lipids. This finding is probably the consequence of long‐lived species having membranes that are exposed to less ROS (Barja, ; Buttemer et al, ; Delhaye et al, ) and that are constitutively less vulnerable to oxidation insults due to their lower PUFA content (Buttemer et al, ; Galván et al, ; Hulbert et al, ; Naudí et al, ). This finding supports a cornerstone prediction of the OSTA and has important implications.…”
Section: Discussionmentioning
confidence: 99%
“…A lower ROS level has obvious physiological advantages, while lower PUFA content renders membranes higher resistance against peroxidative damage (Hulbert, Pamplona, Buffenstein, & Buttemer, 2007;Pamplona et al, 2002). Interspecific comparative studies demonstrated that cell cultures originating from long-lived species are more resistant against oxidative challenges than those of short-lived ones (Harper et al, 2011;Miller, Williams, & Kiklevich, 2011) and that longer lifespan coevolves with a lower rate of ROS generation (Delhaye et al, 2016;Lambert et al, 2007;Pamplona & Barja, 2011;Shi, Buffenstein, Pulliam, & Remmen, 2010) and lower membrane PUFA content (Barja, 2013;Buttemer, Battam, & Hulbert, 2008;Galván et al, 2015;Hulbert et al, 2007;Pamplona & Barja, 2011;Pamplona et al, 2002). A supposed consequence of lower ROS generation and lower membrane PUFA content of long-lived species is their lower level of oxidative lipid damage.…”
mentioning
confidence: 99%